Hollow TiO2 as an Anode for Lithium Ion Batteries: Synthesis and In Situ Visualization of State of Charge. (27th October 2015) - Huang, Xingkang; Cui, Shumao; Wieboldt, Richard C.; Hallac, Peter B.; Fell, Christopher R.; Metz, Bernhard; Jiang, Junwei; Chen, Junhong
Abstract : Hollow TiO2 is synthesized through hydrolysis of titanium tetraisopropoxide on CaCO3 templates to facilitate lithium ion insertion into and extraction from the TiO2 bulk. The hollow TiO2 is capable of delivering 255.9 mAh g −1 with excellent cycling performance. The lithiation mechanism of the TiO2 anode is investigated using an in situ Raman spectroscopic imaging technique.